A rare case of rhabdomyosarcoma in the maxillary alveolar bone: A case report - Abdulrahman Altwaijri; Faraj Alotaiby; Waleed M Alrasheed; Shaul Hameed Kolarkodi (Wolters Kluwer Medknow Publications, 2023)
We report a rare case of spindle cell rhabdomyosarcoma (ScRMS) in a 20-year-old male patient who visited the dental clinic at the Dental Hospital, Qassim University, with an intraoral swelling on the anterior right side of the maxilla, with a subsequent increase in size with tenderness. Clinical, imaging, and histopathological evaluations involving immunohistochemical staining revealed the diagnosis of ScRMS. This report signifies the importance of detailed examination and interdisciplinary collaboration in diagnosing and managing rare tumors.